Efektivitas game komunikata pada mata pelajaran PAIBP di SMP At-Tibyan Pasuruan - Farida, Ayuma Rohmathul; Astutik, Anita Puji (Ta’dibuna: Jurnal Pendidikan Islam, 2021)
Learning strategies that have been realized by educators in Indonesia have achieved various learning models that carry their respective advantages. Therefore, this research aims to determine the level of effectiveness of the communication game learning model. This research uses a quantitative approach with a comparative study model on classroom action research instruments from the results of the first cycle and the results of the second cycle. The average results obtained in the first cycle of 73.4 with a percentage of completeness of 50% while the average in the results of the second cycle of 81.7 with a percentage of completeness of 83.3%. In addition, the results of the correlation test between cycle I and cycle II showed that the correlation coefficient was at a value of 0.278 and a significance value of 0.136. And obtained the results of the hypothesis test based on the results of the paired samples test. So, the results of the statement revealed that there is an influence on the use of communication games on the subjects of Islamic Religious Education and Character Education on students at junior high school At-Tibyan Pasuruan. Abstrak Strategi pembelajaran yang telah direalisasikan oleh pendidik di Indonesia telah mencapai bermacam-macam model pembelajaran yang mengusung kelebihannya masing-masing. Oleh karena itu, penelitian yang dilakukan bertujuan untuk mengetahui tingkat efektivitas model pembelajaran game komunikata. Penelitian ini menggunakan pendekatan kuantitatif dengan model studi komparatif pada instrumen penelitian tindakan kelas dari hasil siklus I dan hasil siklus II. Didapatkan rata–rata pada hasil siklus I sebesar 73,4 dengan persentase ketuntasan sebesar 50% sedangkan rata–rata pada hasil siklus II sebesar 81,7 dengan persentase ketuntasan sebesar 83,3%. Selain itu, hasil pengujian korelasi antara siklus I dengan siklus II didapat hasil koefisien hubungan berada pada nilai 0,278 dan nilai signifikasi 0,136. Serta didapat hasil uji hipotesis berdasarkan hasil pengujian paired samples test. Sehingga hasil pernyataan mengungkapkan bahwa terdapat pengaruh penggunaan game komunikata pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti pada peserta didik di SMP At-Tibyan Pasuruan.